PERSAINGAN USAHA SEHAT DAPAT MEMBANGUN EKOSISTEM BISNIS YANG BERKELANJUTAN - Muhamad Rizki Sudrajat; Zulfahmi Hanifa (Universitas Djuanda, 2023)
Business competition has a healthy positive impact on economic growth and business development. Healthy competition encourages companies to continue to innovate, increase efficiency and improve the quality of their products. In addition, fair competition also contributes to the establishment of a sustainable business ecosystem by encouraging companies to invest in environmentally friendly technologies and carry out ethical and socially responsible business practices. To create fair competition, appropriate business strategies and practices are needed, such as policies and regulations that promote fair competition, effective law enforcement, transparency in business processes, and the establishment of an ethical business culture. Business people must commit to practicing ethical and responsible business values in every aspect of their business.